Neural gliding versus neural tensioning: Effects on heat and cold thresholds, pain thresholds and hand grip strength in asymptomatic individuals. Issue 4 (October 2019) - Gamelas, Tiago; Fernandes, Alexandre; Magalhães, Ivo; Ferreira, Mário; Machado, Solange; Silva, Anabela G.
Abstract: Introduction: Neural mobilization can be performed in a way that facilitates movement through a stretching technique (tensioning) or in a way that maximizes the gliding of peripheral nerves in relation to adjacent structures (gliding). Evidence on how these techniques compare in terms of effects are scarce. The aim of this study is to compare the effects of neural gliding and neural tensioning targeting the median nerve on heat and cold temperature threshold, heat pain threshold, pressure pain thresholds and hand grip strength in asymptomatic participants. Methods: Participants received 4 series of 10 repetitions of either neural gliding (n = 30) or neural tensioning (n = 30) and were assessed for heat and cold temperature threshold, heat pain threshold, pressure pain threshold, and hand grip strength at baseline, immediately after the intervention, and 30 min post-intervention. Results: A significant main interaction between time and intervention was found for the PPT at the forearm (F(2, 55) = 5.98; p = 0.004), favouring the tensioning neural mobilization. No significant differences were found for the other variables. Conclusions: Four series of 10 repetitions of neural tensioning targeting the median nerve in asymptomatic subjects seem to be enough to induce hypoalgesia and have no negative effects on A-delta and C mediated sensory function and on hand grip strength production.